Bacteriocin partitioning from a clarified fermentation broth of Lactobacillus plantarum ST16Pa in aqueous two-phase systems with sodium sulfate and choline-based salts as additives - Sabo, Sabrina da Silva; Lopes, André Moreni [UNESP]; Santos-Ebinuma, Valéria de Carvalho [UNESP]; Rangel-Yagui, Carlota de Oliveira; Oliveira, Ricardo Pinheiro de Souza (Elsevier, 2018)
The partitioning of bacteriocin, a promising alternative to chemical preservatives, in a novel inexpensive and stable aqueous two-phase system (ATPS) comprising poly(ethylene glycol) (PEG) and sodium polyacrylate (NaPA) was studied. The ATPS was generated by mixing both polymers with Na2SO4 or choline chloride ([Ch]Cl) and a bacteriocin extract from the fermented broth of Lactobacillus plantarum ST16Pa. Bacteriocin showed stability at different pH values (3.0–8.0) and temperatures (50–80 °C), as well as in the presence of ATPS components. Hydrophobic and electrostatic interactions were found to be the major driving forces for bacteriocin partitioning. The peptide partitioned preferentially to the PEG-rich phase (partition coefficient, KBact > 1). However, the highest partition coefficient was achieved in the polymeric-based ATPS using [Ch]Cl as additive, as follows: 8 wt% PEG 10,000 g/mol/8 wt% NaPA 8,000 g/mol/0.5 M [Ch]Cl, resulting in a KBact equal to 32. Moreover, these conditions promoted high selectivity (S = 62.7), since the greater part of total proteins partitioned into the NaPA-rich phase (Kprot = 0.51). In conclusion, ATPS composed of PEG/NaPA using choline-based salts as additive can be considered mainly as a first step for bacteriocin extraction from fermented broth by applying low polymer content and mild conditions.
Keywords: Aqueous two-phase system; Bacteriocin partitioning; Choline chloride ([Ch]Cl); Lactic acid bacteria (LAB); Poly(ethylene glycol) (PEG); Sodium polyacrylate (NaPA)